Pengelolaan Kualitas Air pada Pembesaran Udang Vaname (Litopenaeus vannamei) Intensif di PT Varia Indowin Perkasa Desa Alasrejo, Kecamatan Wongsorejo, Banyuwangi, Jawa Timur - Dhea Puspita Hakim; Raihan Bintang Kurniawan Pratama; Taufiq Hidayat; Tubagus Akhmad Al Gifari; Bagus Hidayatullah; Kurnia Putra Yana; Muhammad Fado Al Fajar (Asosiasi Riset Ilmu Tanaman dan Hewan Indonesia, 2025)
This Field Work Practice was carried out at PT Varia Indowin Perkasa (VIP) which is located in Wongsorejo District, Banyuwangi Regency, East Java Province from June 24, 2024 to August 24, 2024. The working method used in this Field Work Practice is a descriptive method with data collection through primary data. Data collection was carried out through active participation, observation, interviews and literature studies. The results of this PKL are monitoring water levels with different results for each plot from 100-130 cm, and water clarity with an average of 56 cm, an average temperature of 26℃. The pH results obtained with an average of 8.4, salinity ranged from 16-24 ppt, nitrite tended to fluctuate with the highest value reaching 0.07 ppm, ammonia 0-0.06. While alkalinity is still stable at 80-120 ppm. The problem in cultivation is the nitrite and ammonia content which exceeds the reasonable limit of 0.3 ppm, so that the water parameters are unstable in the middle of cultivation and the presence of pathogens in the pond waters, including early mortality syndrome and there are cases of shrimp not wanting to eat so that growth is inhibited.